Growth of PbS nanopyramidal particulate films for potential applications in quantum-dot photovoltaics and nanoantennas - Hawaldar, Ranjit R.; Mulik, Uttam P.; Patil, K.; Pasricha, R.; Sathaye, S.; Lewis, A.; Amalnerkar, Dinesh P. (Materials Research Bulletin, 2005)
We report a simple interfacial process called the liquid-liquid interface reaction technique (LLIRT) that leads to the formation of nanosized PbS particulate films with hitherto unreported pyramidal morphology. The resultant PbS films were characterized by transmission electron microscopy (TEM) with selected area electron diffraction (SAED), X-ray diffractometery (XRD), atomic force microscopy (AFM), near field scanning optical microscopy (NSOM) and UV-vis spectroscopy. The pyramidal morphology is speculated to originate from the preferred orientation of the 2 2 0 plane of cubic PbS. Our nanopyramidal PbS particulate films display remarkably sharp excitonic peak centered around 656 nm that accounts for a band gap of 1.8 eV suggesting, in turn, their potential application in QD photovoltaics. Interestingly, the feasibility of such nanopyramids to potentially act as nanoantennas (as revealed by the NSOM) is also suggested. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Atomic force microscopy; Chemical synthesis; Electron microscopy; Nanostructures; Optical properties